Menggali Nilai-Nilai Kepahlawanan TGKH. Muhammad Zainuddin Abdul Madjid Sebagai Sumber Pendidikan Karakter dalam Pembelajaran IPS - Yunitasari, Dukha; Lasmawan, I Wayan; Kertih, I Wayan (Universitas Hamzanwadi, 2023)
The aims of this study were (1) to find out the life history of TGKH. Muhammad Zainuddin Abdul Madjid as National Hero from West Nusa Tenggara Province; (2) Analyze the character values contained in the heroism of TGKH. Muhammad Zainuddin Abdul Madjid in social, da'wah, and education; (3) Analyze the integration of the heroic values of the TGKH. Muhammad Zainuddin Abdul Madjid as a learning resource for social studies subjects at MTs. Mu'allimin NWDI Pancor. Literature research was used to explore the value of heroism TGKH. Muhammad Zainuddin Abdul Madjid. The results showed that TGKH. Muhammad Zainuddin Abdul Madjid is one of the National Heroes from NTB who fought for independence in the fields of preaching and education. The values can be analyzed from the TGKH National Hero figures. Muhammad Zainuddin Abdul Madjid, namely: religious values, nationality, scholarship, brotherhood (cooperation, mutual cooperation), leadership, independence, innovation and creativity, entrepreneurship, and health. The implications of the values of his struggle in shaping the national character of students are the value of awareness of the nature of the struggle in life, the value of awareness in work, the value of awareness of space and time, the value of awareness of the relationship with God Almighty, fellow human beings, and the natural environment. Integrating heroic values TGKH. Muhammad Zainuddin Abdul Madjid was carried out by adding the involvement of values in the indicators developed in the IPS learning syllabus and integrating it through lesson plans and teaching materials.Tujuan dari penelitian ini adalah (1) untuk mengetahui riwayat hidup TGKH. Muhammad Zainuddin Abdul Madjid sebagai Pahlawan Nasional dari Provinsi Nusa Tenggara Barat; (2) Menganalisis nilai-nilai karakter yang terkandung dalam kepahlawanan tokoh TGKH. Muhammad Zainuddin Abdul Madjid dalam bidang sosial, dakwah, dan pendidikan; (3) Menganalisis integrasi nilai-nilai kepahlawanan tokoh TGKH. Muhammad Zainuddin Abdul Madjid sebagai sumber belajar pada mata pelajaran IPS di MTs. Mu'allimin NWDI Pancor. Penelitian kepustakaan digunakan untuk menggali nilai kepahlawanan TGKH. Muhammad Zainuddin Abdul Madjid. Hasil penelitian menunjukkan bahwa TGKH. Muhammad Zainuddin Abdul Madjid adalah salah satu Pahlawan Nasional asal NTB yang memperjuangkan kemerdekaan di bidang dakwah dan pendidikan. Nilai-nilai tersebut dapat dianalisis dari tokoh-tokoh Pahlawan Nasional TGKH. Muhammad Zainuddin Abdul Madjid, yaitu: nilai-nilai religius, kebangsaan, keilmuwan, ukhuwah (kerja sama, gotong royong), kepemimpinan, kemandirian, inovasi dan kreativitas, kewirausahaan, dan kesehatan. Implikasi nilai-nilai perjuangannya dalam membentuk karakter bangsa peserta didik adalah nilai kesadaran hakikat perjuangan dalam hidup, nilai kesadaran dalam berkarya, nilai kesadaran ruang dan waktu, nilai kesadaran akan hubungan dengan Tuhan Yang Maha Esa, sesama manusia, dan alam lingkungan. Mengintegrasikan nilai-nilai kepahlawanan TGKH. Muhammad Zainuddin Abdul Madjid dilakukan dengan menambahkan keterlibatan nilai dalam indikator yang dikembangkan dalam silabus pembelajaran IPS dan mengintegrasikannya melalui RPP dan bahan ajar.